Meningkatkan Pemahaman Karir Menggunakan Bimbingan Kelompok melalui Media Art And Craft pada Siswa - Suhaida Suhaida; Syska Purnama Sari; Endang Surtiyoni (Journal on Education, 2024)
Developing professional understanding is essential to enable them to make informed career decisions and develop optimally. To fulfill this expectation, which aims to ensure that students' self-image and professional understanding increases significantly, this study aims to determine whether there is an influence in group guidance using art and craft media on students where researchers use an experimental quantitative research methodology, namely experimental design which is research to look for the effect of a treatment. To support the success of researchers to strengthen research by using purposive sampling. The sample in this study were 15 students who had low career understanding. Based on the results of the study and discussion, it can be concluded that the control group used Art anad Craft media was effective in increasing career understanding, this can be seen through the results of the pretest by distributing career understanding questionnaires where there were 15 students who did not understand careers, experienced an increase in career understanding scores, namely high. From 44.12% to 73.80% after Art and Craft media. Having carried out group guidance through art and craft greatly increased students' understanding of careers. The results of the hypothesis show that there are differences in career understanding. students before and after this treatment were confirmed by the results of the Wilcoxon test. With a significance value of 0.001, which means 0.001 > 0.05, the hypothesis put forward in this study is accepted, so it can be concluded that there is a significant influence between the provision of group guidance services using art and craft media on the professional understanding of students of SMP Negeri 16 Palembang. The researcher hopes that this research will be useful to find out the effectiveness of group guidance through art and craft media in fostering students' interests and talents in determining their future.